Spectral Data Analysis and Identification of Vancomycin Hydrochloride - Tian, Ye; Chong, Xiaomeng; Yao, Shangchen; Xu, Mingzhe (Frontiers in Chemistry, 2021)
Objective: To establish a method for the determination of the chemical structure of vancomycin hydrochloride. Methods: Nuclear magnetic resonance spectroscopy and mass spectrometry were conducted to analyze the chemical structure of vancomycin hydrochloride. Results: In this study, the target compound (1) was identified as (Sα)-(3S, 6R, 7R, 22R, 23S, 26S, 36R, 38αR)-44-[[2-O-(3-amino-2, 3, 6-trideoxy-3-C-methyl-α-L-lyso-hexopyranosyl)-β-D-glucopyranosyl] oxy]-3-(carbamoylmethyl)-10, 19-dichloro-7, 22, 28, 30, 32-pentahydroxy-6-[[(2R)-4-methyl-2-(methylamino) pentanoyl] amino]-2, 5, 24, 38, 39-pentaoxo-2, 3, 4, 5, 6, 7, 23, 24, 25, 26, 36, 37, 38, 38α-tetradecahydro-22H-8, 11: 18, 21-dietheno-23, 36-(iminomethano)-13, 16: 31, 35-dimetheno-1H, 13H-[1, 6, 9] oxadiazacyclohexadecino [4, 5-m] [10, 2, 16]-benzoxadiazacyclotetracosine-26-carboxylic acid hydrochloride. Conclusion: The method used in this study is accurate and can be used for the production and structural elucidation of vancomycin hydrochloride.